Предмет: Алгебра,
автор: silv2000
корень из (3 - корень из 6)^2 + корень из (2 - корень из 6)^2
Ответы
Автор ответа:
0
3 - √6 = √9 - √6 > 0
√(x²) = |x| = x, если x>=0
√(x²) = |x| = -x, если x<0
√(3-√6)² = 3 - √6
2 - √6 = √4 - √6 < 0
√(2 - √6)² = -(2-√6) = √6 - 2
Ответ: 1
√(x²) = |x| = x, если x>=0
√(x²) = |x| = -x, если x<0
√(3-√6)² = 3 - √6
2 - √6 = √4 - √6 < 0
√(2 - √6)² = -(2-√6) = √6 - 2
Ответ: 1
Похожие вопросы
Предмет: Литература,
автор: dianazaderej
Предмет: Математика,
автор: altin21081985
Предмет: Другие предметы,
автор: musaevaguzela39
Предмет: Физика,
автор: Аноним
Предмет: Алгебра,
автор: sasha11991